Propuesta de diseño del sistema de gestión de seguridad y salud en el trabajo para el traslado de nitrato de amonio de Trujillo a Cajamarca por la empresa de transporte Santa Brigida SRL. - Urquiaga Robles, Lisseth Milagros (2017)
ABSTRACT The present work aims to propose the design of the Occupational Health and Safety Management System to reduce the accident rate when transporting ammonium nitrate from Trujillo to Cajamarca by the transport company Santa Brígida, based on National and Standard International OHSAS 18001: 2007. Requirements, interviews, direct observations, document review 2007 Management System Safety and Health at Work: checklists guidelines Management System Safety and Health at Work based on Standard OHSAS 18001 was used. First was the diagnosis of the current situation Safety and Health at Work and subsequently the proposal was made. The results of the assessment of the current security situation and health of the company show that it has implemented 43.5% in compliance with the requirements. Finally, the proposed design of health and safety system was developed. It concludes; that the transport company Santa Brígida S.R.L, in terms of safety and health has weaknesses in the implementation and therefore the application of the proposed design can reduce the accident rate in the transport of ammonium nitrate.